A mediação de conflitos em espaços educacionais – contribuições da biologia do amor e da biologia do conhecimento de Humberto Maturana - Silva, Edem Alexandre da (2021)
This Master's Thesis work is linked to the Postgraduate Program in Education, in the Research Line: Teaching, Knowledge and Professional Development – LP1 (PPGE-UFSM). The study has as its theme the research on the action of mediating educational conflicts: converging lines between the mediation of conflicts and intercultural education, considering the possibility of the teacher to act in the mediation of such conflicts, having interculture as a base theory. Therefore, the research problem revolves around: to what extent can the teacher act as a mediator of conflicts, using the assumptions of interculturality and its influence to build a more peaceful education? Thus, the research focused on the teacher as a possible mediator in the school context, based on Humberto Maturana's dialogue and love. The study aims to present mediation and its possibilities, with the intention of, through academic dialogue and its analysis, contributing to new teacher images and to the continuing education of teachers, with a focus on education in the 21st century. This study is relevant, as it provides opportunities for teachers at all levels of current education to reflect that the ―teacher‖ is more than a facilitator and guide in education. He can serve as a mediator of conflicts between students and the student's intimate conflict with himself or with the school community. Mediating is not always between two people, but the person with himself, in his internal conflict, facing a new reality that is the school environment. Mediating a conflict is to focus efforts on valuing the individual. And mediating a school conflict is a sublime act of conditioning that human being to the experiences of love, through the Biology of Love by Humberto Maturana. When a conflict arises in the classroom, it is time to reflect, dialogue and mediate. These conditions and possibilities are the differential in school mediation, in the intercultural relationship of being. It is, therefore, a qualitative research, with a bibliographic nature and an epistemological perspective, which seeks to contribute to reflections on teacher education.